The Influence of Channel Planform and Slope Topography on Turbidity Current Overbank Processes: The Example of the Acquarone Fan (Southeastern Tyrrhenian Sea) - Scacchia, Elena; Tinterri, Roberto; Gamberi, Fabiano (Frontiers in Earth Science, 2022)
Overbank deposits provide a potentially valuable record of flows that have passed through a submarine channel. The architecture of overbank deposits has generally assumed to relate to autogenic processes related to channel construction. In previous models, which are largely based on passive margins, the distribution and geometry of these deposits is relatively simple, and hence generally predictable. Here, we show how the interaction of different flow types with the complex morphology on a highly-tectonically modified margin can profoundly affect overbank depositional processes, and hence also the resultant deposit geometry and architecture. Our case study is the Acquarone Fan, located in the intraslope Gioia Basin in the south-eastern Tyrrhenian Sea, whose topography is mainly controlled by the presence of the Acquarone structural ridge, which results in the confinement of the left south-west side of the channel-levee system. The research is carried out through analysis of multibeam bathymetric and high-resolution Chirp sub-bottom profiler data. Seven depositional units (Units I-VII) record the recent depositional history of the fan; their thickness has been mapped and their parent flow-types have been interpreted through their seismic response. According to unit thickness maps, two main patterns of deposition are recognized in the overbank area. Their depocenters coincide with different extensive sediment wave fields developed in specific tracts of the right levee and in the frontal splay area. We show that the location of the depocenters varies in time according to the prevalent flow-type and by its interaction with the surrounding seafloor topography and channel planform. We interpret that the lateral confinement of the channel by the structural high generates episodic rebound of the overspilling flow and the inversion of the channel asymmetry. The vertical stratification of the flow strongly influences the overbank deposition where the channel planform has a non-linear shape such as bends and knick-points. In particular, the vertical stratification influences the hydraulic jump size that conditions the amount of overspill and thus the location of overbank depocenters. This study highlights that variations in the sediment distribution and composition on the overbank can be related to the way different flows interact with tectonic setting.